Efektivitas Layanan Konseling Kelompok dengan Teknik Self-Regulated Learning dalam Meningkatkan Motivasi Belajar Siswa - Delta Embong Bulan; Selviana Mangalik; Elga Maya Pairunan (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2026)
This study aims to explore the effectiveness of group counseling services integrated with self-regulated learning (SRL) techniques in enhancing students’ learning motivation. Learning motivation is a crucial factor influencing academic achievement, yet many students still experience low motivation due to various internal and external challenges. The integration of SRL is considered beneficial as it encourages students to actively manage their learning processes through goal setting, self-monitoring, and reflective evaluation. This research employs a literature review approach by examining recent and relevant academic sources. The findings indicate that the application of SRL within group counseling contributes positively to students’ motivation, as reflected in increased participation, improved learning discipline, and stronger responsibility toward academic tasks. Furthermore, students demonstrate better ability in organizing their learning activities and maintaining consistency in achieving learning objectives. These results suggest that SRL-based group counseling can serve as an effective strategy for school counselors in supporting students’ academic motivation and engagement.